Energy efficiency and server virtualization in data centers : an empirical investigation - Yichao Jin. (2013)
With a growing concern on the considerable energy consumed by data centers, research efforts are targeting toward green data centers with higher energy efficiency. In particular, server virtualization is emerging as the prominent approach to consolidate applications from multiple applications to one server, with an objective to save energy usage. However, little understanding has been obtained about the potential overhead in energy consumption and the throughput reduction for virtualized servers in data centers. In this research, we take the initiative to characterize the energy usage on virtualized servers. An empirical approach is adopted to investigate how server virtualization affects the energy usage in physical servers. Through intensive data collection and analysis, we identify a fundamental trade-off between the energy saving from server consolidation and the detrimental effects (e.g., energy overhead and throughput reduction) from server virtualization. This characterization lays a mathematical foundation for server consolidation in green data center architecture.